2016
DOI: 10.1016/j.phrs.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Higenamine protects ischemia/reperfusion induced cardiac injury and myocyte apoptosis through activation of β2-AR/PI3K/AKT signaling pathway

Abstract: Cardiomyocyte apoptosis contributes to ischemic cardiac injury and the development of heart failure. Higenamine is a key component of the Chinese herb aconite root that has been prescribed for treating symptoms of heart failure for thousands of years in the oriental Asian countries. It has been shown that higenamine has anti-apoptotic effects in a few cell types including cardiomyocytes. However, the pharmacological target and molecular mechanism of higenamine in the heart are still not fully illustrated. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 26 publications
3
61
1
Order By: Relevance
“…Meanwhile, an upregulation of G i is often associated with enhanced β 2 AR-Gi signaling in HF. The enhanced β 2 AR-G i signaling leading to Akt activation can protect against myocyte apoptosis, and consequently slow down the progression of cardiomyopathy [26]. Therefore, a combined therapy of β 1 AR blocker and β 2 AR agonist has been proposed for treatment of HF.…”
Section: Desensitization Of Cardiac βArs In Heart Failurementioning
confidence: 99%
“…Meanwhile, an upregulation of G i is often associated with enhanced β 2 AR-Gi signaling in HF. The enhanced β 2 AR-G i signaling leading to Akt activation can protect against myocyte apoptosis, and consequently slow down the progression of cardiomyopathy [26]. Therefore, a combined therapy of β 1 AR blocker and β 2 AR agonist has been proposed for treatment of HF.…”
Section: Desensitization Of Cardiac βArs In Heart Failurementioning
confidence: 99%
“…Studies have also demonstrated an important role of apoptosis in ischaemic heart disease, contributing to myocyte cell death in MI and left ventricular remodelling . To examine whether this model is applicable to study cardiac myocyte apoptosis induced by MI, we detected the apoptosis by TUNEL.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also demonstrated an important role of apoptosis in ischaemic heart disease, contributing to myocyte cell death in MI and left ventricular remodelling. 27 To examine whether this model is applicable to study cardiac myocyte apoptosis induced by MI, we detected the apoptosis by TUNEL. As shown in Figure 6B, the apoptosis rate of cardiac myocyte in ischaemic area was completely increased in mice with the surgeries of both traditional method and new method, compared to sham mice.…”
Section: New Methods Of Mim Surgery Induces Cardiac Myocyte Apoptosismentioning
confidence: 99%
“…Adult mouse cardiomyocytes were isolated from hearts of C57BL/6J mice by enzymatic dissociation using collagenase type II in a Langerdorff perfusion system, according to a previously described protocol with modification [14]. In brief, heparinized and anesthetized mouse heart were rapidly excised, cannulated, and perfused with Ca 2+ free isolation buffer (120 mM NaCl, 15 mM KCl, 0.6 mM KH 2 PO 4 , 0.6 mM Na 2 HPO 4 , 4.6 mM NaHCO 3 , 1.2 mM MgSO 4 , 10 mM HEPES, 30 mM taurine, 5.5 mM glucose, 10 mM 2,3-butanedione monoxime (BDM), 10 mM creatine monohydrate, pH 7.4) for 3 min followed by collagenase type II (Worthington) mixed isolation buffer (50 mg in 50 mL isolation buffer, 40 nM CaCl 2 ) until digestion was complete.…”
Section: Methodsmentioning
confidence: 99%